Pengaruh struktur kepemilikan terhadap mekanisme IT governance berdasarkan kerangka cobit 5 dengan budaya Hofstede sebagai intervening - Aprinovitadevie , Yosephine Wigathi; Chrismastuti, Agnes Advensia (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This study aims to examine the effects of Hofstede's five cultures, namely Power Distance (PD), Individualism (IC), Uncertainty Avoidance (UA), Femininity (MF), and Confucian Dynamism (CD) as well as ownership structure, which is divided into two, namely business ownership by individuals / families and business ownership by corporations / non-families on the quality of IT Governance implementation in companies seen by the CobiT 5 Framework, especially from the Evaluate, Direct and Monitoring Domain. This study provides a theoretical contribution regarding the adjustment of the COBIT model needed to be implemented in developing companies in Indonesia; especially in Central Java, it will also provide empirical evidence regarding the influence of Hofstede's cultural dimensions on IT governance in the COBIT 5 framework, especially in the EDM domain; and this study found, that for the overall relationship, only the Confucian Dynamism variable has a significant influence as an intervening between the Ownership Structure variable and IT Governance, which is due to certain principles and views for running a business that influence company owners in determining policies on IT Governance that will be used to support company operations.